Volume 5: Turbo Expo 2007 2007
DOI: 10.1115/gt2007-27196
|View full text |Cite
|
Sign up to set email alerts
|

Tools for Estimating Resonant Stresses in Turbine Blades

Abstract: The problem of obtaining adequate aerodynamical boundary conditions for an analyzed blade is important to predict resonant stresses. According to this, three different CFD approaches of stator-rotor modeling have been investigated for obtaining gas dynamic loading: 1. 3D averaged and then quasi-3D unsteady calculations. 2. Fully 3D unsteady calculations using commercial CFX solver. 3. Fully 3D unsteady calculations using the in-house solver. To carry out 3D structural analysis the ANSYS software and our subrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The authors concluded that blade forced-response and the high-cycle fatigue failures that can result from it are of sufficient interest to the gas-turbine community that " : : : a decrease in the level of empiricism [in that area] would be of significant value in the engine development process." Accordingly, many companies now include calculations of resonant stresses in multirow turbomachinery in their design processes [10][11][12][13][14][15][16].…”
mentioning
confidence: 99%
“…The authors concluded that blade forced-response and the high-cycle fatigue failures that can result from it are of sufficient interest to the gas-turbine community that " : : : a decrease in the level of empiricism [in that area] would be of significant value in the engine development process." Accordingly, many companies now include calculations of resonant stresses in multirow turbomachinery in their design processes [10][11][12][13][14][15][16].…”
mentioning
confidence: 99%